Central role of Galectin-3 at the cross-roads of cardiac inflammation and fibrosis: implications for heart failure and transplantation - Seropian, Ignacio M. (2024)
Fil: Seropian, Ignacio M. Hospital Italiano de Buenos Aires; Argentina